Lifting the lid of the "black intervention box" - the systematic development of an action competence programme for people with screen-detected dysglycaemia - Maindal, Helle Terkildsen (BioMed Central, 2010)
BACKGROUND: The evidence gained from effective self-management interventions is often criticised for the ambiguity of its active components, and consequently the obstruction of their implementation into daily practice. Our aim is to report how an intervention development model aids the careful selection of active components in an intervention for people with dysglycaemia. METHODS: The first three phases of the UK Medical Research Council's model for developing complex interventions in primary care were used to develop a self-management intervention targeting people with screen-detected dysglycaemia. In the preclinical phase, the expected needs of the target group were assessed by review of empirical literature and theories. In phase I, a preliminary intervention was modelled and in phase II, the preliminary intervention was pilot tested. RESULTS: In the preclinical phase the achievement of health-related action competence was defined as the overall intervention goal and four learning objectives were identified: motivation, informed decision-making, action experience and social involvement. In Phase I, the educational activities were defined and the pedagogical tools tested. In phase II, the intervention was tested in two different primary healthcare settings and adjusted accordingly. The 18-hour intervention "Ready to Act" ran for 3 months and consisted of two motivational one-to-one sessions conducted by nurses and eight group meetings conducted by multidisciplinary teams. CONCLUSIONS: An intervention aimed at health-related action competence was successfully developed for people with screen-detected dysglycaemia. The systematic and transparent developmental process is expected to facilitate future clinical research. The MRC model provides the necessary steps to inform intervention development but should be prioritised according to existing evidence in order to save time.